2012
DOI: 10.1002/lary.23552
|View full text |Cite
|
Sign up to set email alerts
|

Scalp as split thickness skin graft donor site for congenital atresia repair

Abstract: Objective: Describe the use of the scalp as a donor site for split thickness skin grafts in otologic surgery. Materials and Methods: Review of the literature with detailed description of surgical technique and authors' experience.Results: One hundred and forty-four scalp split thickness skin grafts were obtained between 2007 and 2011. No significant complications were observed with optimal cosmetic results.Conclusions: The scalp is a viable option as a split thickness skin graft donor site for otologic and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…Only one patient preferred the leg as donor site in order to be able to better conceal the secondary scar. Used once in our patient group, the scalp has also been reported to be a suitable donor site for skin grafting . Faced with this option, elderly patients in particular did not want to have their scalp shaved.…”
Section: Discussionmentioning
confidence: 98%
“…Only one patient preferred the leg as donor site in order to be able to better conceal the secondary scar. Used once in our patient group, the scalp has also been reported to be a suitable donor site for skin grafting . Faced with this option, elderly patients in particular did not want to have their scalp shaved.…”
Section: Discussionmentioning
confidence: 98%
“…Many articles reported that patients' heads were shaved using a razor. It is difficult to remove the hair shaft from grafts; thus, the hair shaft was trimmed to a length of 1-2 mm to allow easier subsequent hair removal [20,21].…”
Section: Harvesting Techniquementioning
confidence: 99%
“…The tumescent solution in four articles was mixed with anesthetic agents, such Mean (range) or mean ± SD (range); b) Refers to early systemic complications. as 0.5% lignocaine [5], 0.25%-0.5% prilocaine [17], 1% prilocaine [25], and 0.06% bupivacaine [20]. Additionally, in 16 articles, the solutions were mixed with adrenaline [7] at ratios of 1:10,000 [25], 1:100,000 [12,16], 1:200,000 [5,17], 1:250,000 [22], 1:300,000 [14], 1:500,000 [18,22,26], 1:600,000 [21], 1:800,000 [4,20] 1:1,000,000 [15,19] and 1:2,000,000 [11,21].…”
Section: Harvesting Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Lediglich ein Patient bevorzugte den Oberschenkel als Spenderregion, um die zweite Narbe besser verstecken zu können. Auch die Kopfhaut wurde als gute Spenderregion für Hauttransplantate beschrieben . Wir nutzten diese Region einmal.…”
Section: Diskussionunclassified